Comparison of vertical forces between a pressure measurement system and a force plate - Brisson, N.; Kendall, M. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Force plates and pressure measurement systems are commonly used for clinical and experimental applications. The MatScan (Tekscan Inc.), a lightweight, portable and cost-efficient pressure mapping system, can serve as an alternative to a force plate for measuring vertical forces. There has been much debate, however, as to the accuracy and precision of pressure mapping systems when compared to force plates, which have been considered the gold standard in force measurement (Hsiao, Guan & Weatherly, 2002). Although much research has been conducted using different force and pressure measurement systems, there is virtually no literature that discusses the comparisons of measured forces between these types of systems. The goal of this study was to compare the vertical forces measured by the MatScan to those measured by an AMTI force plate.